Effect of Vehicle-to-Vehicle Communication Latency on a Collision Avoidance Algorithm for Heavy Road Vehicles - Yellapantula, Venkata Ramani Shreya; Rao, Rakesh N.; Subramanian, Shankar C. (2018 IEEE Intelligent Vehicles Symposium (IV), 2018)
Active safety is of utmost importance in heavy road vehicles due to the relatively higher number of fatalities encountered in their accidents. Vehicle-to-Vehicle (V2V) technology, which is seen as a future of connected vehicles, can potentially complement onboard sensing to reduce the time taken for detection, and to plan the path with the information available from road side units (RSU). This paper investigates the effect of Iatency in (V2V) communication on a collision avoidance algorithm developed for heavy road vehicles. Experiments performed on a Hardware-in-Loop (HiL) setup were used to evaluate the effect of Iatency for various scenarios. It was found that Iatency had a counterbalancing effect on vehicle spacing and relative longitudinal speed that led to insignificant changes in the final spacing. Further, a sensitivity analysis done at different host vehicle longitudinal speeds demonstrated the need of a variable time headway.